Hypothesis: Etiologic and Molecular Mechanistic Leads for Sporadic Neurodegenerative Diseases Based on Experience With Western Pacific ALS/PDC - Spencer, Peter S. (Frontiers in Neurology, 2019)
Seventy years of research on Western Pacific amyotrophic lateral sclerosis and parkinsonism-dementia (ALS/PDC) has provided invaluable data on the etiology, molecular pathogenesis and latency of this disappearing environmental neurodegenerative disease. ALS/PDC is linked to genotoxic chemicals (notably methylazoxymethanol, MAM) derived from seed of the cycad plant (Cycas spp) which was used as a traditional food and/or medicine in all three affected Western Pacific populations. MAM, nitrosamines and hydrazines generate methyl free radicals which damage DNA (O6-methylguanine) that can induce mutations in cycling cells and degenerative changes of post-mitotic cells, notably neurons. The paper examines evidence that link exposure to naturally occurring and manmade sources of nitrosamines and hydrazines to sporadic forms of ALS (with or without frontotemporal degeneration), progressive supranuclear palsy, and Alzheimer disease. Research approaches are offered to test this unifying hypothesis.